Vortices of the Mozambique ridge current - Gründlingh, Marten Luther (Department of Oceanography, 2016)
During a cruise of the R.V. Meiring Naude in August 1975, anomalous values for temperature, salinity and nutrients were recorded over a deep-sea region of the Southwestern Indian Ocean. It was thought that this oceanographic anomaly may represent part of a cyclonic mesoscale vortex of unknown origin. The scant information available at the time on the circulation in this area precluded any of the known, steady currents from being possible generators. Only once before, in 1962, had a similar observation been made, and its significance had not been recognised. In the period 1976 to 1982, several hydrographic cruises were executed on the R.V. Meiring Naude in the region 27 - 33°S, 32 - 43°E, to locate similar features and to find answers to the following questions: Was the 1975 anomaly really a vortex (i.e. a rotating body of water)? What are the physical and dynamic characteristics (i.e. temperature, salinity, density, velocity, volume transport, energy) and distribution of such vortices? How and where are the vortices generated, and what are their lifetime and eventual fate? In all, more than 500 routine hydrographic stations were occupied to collect data on water properties. Most of these stations extended to a depth of 1 000 m, while about 20% went to at least 1 800 m. Initially, hydrosondes designed and built by the Council for Scientific and Industrial Research were employed, but a Neil Brown Instrument Systems' CTD (conductivity-temperature-depth) microprofiler was used from 1979 onwards. Satellite-tracked buoys and infrared imagery were used to derive information on the circulation patterns, thus extending the coverage of the small research vessel. The drift rate of the ship and current measurements from a drifting array of current meters augmented the calculations of geostrophic velocity, volume transport and energy, and provided insight into the flow dynamics of the water.